Right submandibular gland metastasis from an occult papillary thyroid cancer - Radia, Sheetal; Singh, Chandra Veer; Chamoli, Priyanka (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Papillary microcarcinoma may present with clinical symptoms, most commonly jugulodigastric and pretracheal lymphadenopathy with or without palpable thyroid nodules. Isolated submandibular metastases are rare. We are presenting here a case report of 40-year old lady with an isolated submandibular gland metastasis arising from a papillary thyroid carcinoma. Submandibular gland excision of right side was done based on the fine needle aspiration cytology (FNAC) which suggested features of Basal cell adenoma vs cellular pleomorphic adenoma. USG neck s/o 3×3.5×2.8 cm sized hypoechoic lesion right submandibular. Histopathologic examination of the specimen suggested a metastatic papillary carcinoma. Total thyroidectomy was done, no other site of metastasis was found on radio-iodine scanning.